MEMBANGUN KARAKTER ANAK DENGAN BUDAYA KEARIFAN LOKAL DALAM PROSES PEMBELAJARAN DI SEKOLAH - Sudarmiani Sudarmiani (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
In the current era of globalization, the challenges before us as a nation is the ability to put the strength of character as a nation.Therefore,the implementation of policy and character-based education in schools is very important and strategic in order to build this nation. Local knowledge can serveas a source of values for then oble purpose.In other words, local knowledge can be a well that never dry as the source of values for the realization of policy goals  nation.In addition to functioning as a filter for the values that come from outside, local wisdom can also be used to increase motivation, perseverance, tolerance, and reduce flare-ups that are internal.Build the character of students to do during the learning process takes place. In each of the learning process we can always  tuck load the values of honesty, courage, perseverance and tenacity, confident attitude, diligent study and work, respect for   teachers, respect and care for the others, life is tough does not know the word surrender and positive attitude other. Some wise  words that are part of the local wisdom can be used as the basis to develop character values in the learning process. Wise sentence can be used to motivate the students to build a positive attitude.